2013
DOI: 10.2478/ppb-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Don’t pay attention to what you see! Negative commands and attention bias

Abstract: The paper presents research into the effects of the use of negations in directives (orders, suggestions, requests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…This means that a negation sign preceding a given word does not inhibit its affective valence. A series of studies [ 61 ] on the effects of negative injunctions on directing the attention of recipients has shown that negative directives (commands, suggestions, requests) trigger a paradoxical or counter-effective effect; after receiving a request not to pay attention to object X, participants automatically focused their attention on that object (to a similar degree as participants who were asked directly to pay attention to the given object). In some research [ 62 ], negating stereotypes enhanced the activation of stereotypes and negative evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…This means that a negation sign preceding a given word does not inhibit its affective valence. A series of studies [ 61 ] on the effects of negative injunctions on directing the attention of recipients has shown that negative directives (commands, suggestions, requests) trigger a paradoxical or counter-effective effect; after receiving a request not to pay attention to object X, participants automatically focused their attention on that object (to a similar degree as participants who were asked directly to pay attention to the given object). In some research [ 62 ], negating stereotypes enhanced the activation of stereotypes and negative evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…In the classic demonstration, subjects were more likely to think about a white bear after a 5‐min period with instructions not to think about a white bear than if they had not received these instructions (Wegner et al, 1987). Similarly, subjects who read a comic book excerpt had better memory for information related to a specific character when they were instructed to pay attention to the character or when they were instructed not to pay attention to the character compared to a control condition with no instructions regarding the character (Maciuszek, 2013). These studies demonstrate that, under certain circumstances, negation can increase the processing of negated information.…”
Section: Introductionmentioning
confidence: 99%
“…We had presumed delayed responses to be the result of an increased focus on words related to purification, but our findings call this into question. It has been reported that increased attention paid to objects results in longer RTs to them, as well as in better recall of them in subsequent memory tests (Maciuszek, 2013). However, the results of Study 3 suggest that thinking about one's own immoral behavior led participants to remember fewer words associated with body cleansing (in comparison to the control condition).…”
Section: Discussionmentioning
confidence: 61%
“…We presumed that, in situations of morality threats, people doing the LDT will pay more attention to words related to cleansing. Due to the fact that intentionally focusing attention on detected stimuli leads to slower RTs (Maciuszek, 2007(Maciuszek, , 2013, we predicted that, when primed with an immoral action, we will see a delay in RTs to phrases associated with purifying in the LDT. In this way, we tested whether thinking about one's own moral transgressions results in slower RTs to words connected with body cleansing while thinking about the moral transgressions of someone else results in slower RTs to stimuli related to purifying the external world.…”
Section: The Influence Of the Metaphor "Morality Is Purity" On Moral mentioning
confidence: 99%